Interpretasi makna peribahasa dalam pidato abu ubaidah - Berliana, Dinar (Maliki Interdisciplinary Journal, 2025)
This study aims to elucidate the significance of proverbs utilized by Abu Ubaidah in his discourses. To this end, a content analysis of speech transcripts accessible on the YouTube channel "Arab Tutor" was conducted. A descriptive qualitative approach was employed to analyze the proverbial utterances identified, with a particular focus on uncovering idiomatic meanings. The findings indicate that all the data obtained contain idiomatic meanings. Consequently, it can be posited that Abu Ubaidah’s deployment of proverbs in his discourses consistently reflects the expression of profound idiomatic meanings. The proverbs used by Abu Ubaidah in his speech also have deep idiomatic meanings, each depicting the strength, helplessness of the enemy, and the determination of the people of Gaza to defend their territory. Thus, these proverbs not only adorn his speech, but also reinforce the important messages he conveys to the world.